Psoriasis and dementia: A population‐based matched cohort study of adults in England - Julian Matthewman; Kathryn E. Mansfield; Sharon L. Cadogan; Katrina Abuabara; Catherine Smith; Krishnan Bhaskaran; Sinéad M. Langan; Charlotte Warren‐Gash (Annals of Clinical and Translational Neurology)
Abstract Objective Evidence for an association between psoriasis and dementia is limited and conflicting. We aimed to investigate the association using large and representative population‐based data and describe risk by dementia subtype and over time. Methods We compared dementia risk between people with and without psoriasis using an age‐, sex‐ and primary care practice‐matched cohort of adults aged ≥40 years from the Clinical Practice Research Datalink Aurum in England (1997–2021) linked to hospital admissions data, analysed with stratified Cox regression. Results Among 360,014 individuals with psoriasis and 1,799,617 without, psoriasis was associated with a small increased risk of all‐cause dementia (adjusted hazard ratio [aHR] 1.06, 95% CI 1.04–1.08; absolute rate difference 24 per 100,000 person‐years). Strength of association increased with time since psoriasis diagnosis (e.g. aHR 0.99, 0.96–1.03 within 0 to 5 years; 1.20, 1.05–1.37 within 20 to 25 years). The association was stronger for vascular dementia (aHR 1.10, 1.06–1.14) than Alzheimer's dementia (aHR 1.03, 1.00–1.06). Hazard ratios were larger for severe psoriasis (all‐cause aHR 1.32, 1.25–1.39; vascular aHR 1.58, 1.44–1.74; Alzheimer's aHR 1.11, 1.02–1.21). Interpretation Long‐term risk of all‐cause dementia and vascular dementia, but not Alzheimer's dementia, was slightly higher in people with psoriasis, but absolute risk differences were small. Risks were more substantially raised with time since psoriasis diagnosis and in severe psoriasis compared to mild to moderate psoriasis, suggesting a potential dose–response relationship.